IMPLEMENTASI KURIKULUM ISLAM DAN LINGKUNGAN PENDIDIKAN YANG TERINTEGRASI DALAM MENINGKATKAN HASIL BELAJAR - Badratul Laela, Neng Linda (PUSDATIN Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2024)
Integrated Islamic primary schools are seen to act as Anasirit Taghyiir (gene change), escorting and directing social and cultural change. In this case, researchers are interested in conducting research on Primary schools. The research methods that will be used are descriptive, qualitative, and empirical approaches to the theory of